Globalization and income inequality : evidence from BRICS countries and Turkey - Bahadir, Büşra (My University, 2019)
Geçtiğimiz otuz yıl boyunca çoğu ülkede, özellikle gelişmekte olan ülkelerde, gelir eşitsizliği önemli ölçüde arttı ve bu durum yaygın bir endişe haline geldi. Ülkelerde artan gelir eşitsizliği malların, hizmetlerin, sermayenin ve emeğin uluslararası sınırlar arasında dolaşımının artması yolu ile ülkelerin küreselleşmeye maruz kaldıkları döneme denk gelmektedir. Bu tez, Türkiye ve BRICS ülkelerinden oluşan bir paneli kullanarak 1990-2015 yılları arasındaki küreselleşme (finansal ve ticaret değişkenleri ile ölçülen) ve gelir eşitsizliği arasındaki ilişkiyi incelemektedir. Ekonometrik model uygun panel veri teknikleri kullanılarak tahmin edilmiştir. Bulgulara göre, finansal küreselleşme sermaye hesabı açıklığı indeksi ve borsa cirosu oranı kanalıyla 1990’dan beri bu ülkelerde gelir eşitsizliğinin itici gücü olurken, ithalat ve ihracat kanalı ile dışa açıklık ise gelir eşitsizliğini artıran bir etki sergilemektedir. İleri teknoloji ihracatının mutlak beceri yanlılığı etkisi ampirik bulgularla kanıtlanmıştır. Diğer bulgular özel kredilerin, nüfus artışının ve tüketici fiyat endeksinin küreselleşmenin faydalarının eşit olmayan şekilde dağılmasına neden olduğunu göstermektedir.

Income inequality has increased dramatically in the most countries, especially in developing countries, over the past three decades and it has became a widespread concern. The widening income disparity within countries has coincided with the process which countries increasingly exposed to the globalization through increased flows of goods, services, capital and labour across international borders. This thesis examines the relationship between globalization (measured with both financial and trade variables) and income inequality using a panel of Turkey and the BRICS countries over the period 1990–2015. The econometric model is estimated by using convenient panel data techniques. The findings indicate that trade openness through import and export channel exhibits a disequalizing impact, while financial globalization with the channel of capital account openness and stock market turnover rate has been the driving force of income inequality in these countries since 1990. The absolute skill-bias impact of high technology export is evidenced by empirical results. Other findings exhibit that private credit, population growth and consumer price index allow the benefits of globalization to be shared unequally.
Keywords: Finance; Gelir Eşitsizliği; Income Inequality; Küreselleşme; Maliye; Panel Data; Panel Veri Globalization